Mental health profiles of Finnish adolescents before and after the peak of the COVID-19 pandemic - Jasmine Gustafsson; Nelli Lyyra; Inga Jasinskaja-Lahti; Nina Simonsen; Henri Lahti; Markus Kulmala; Kristiina Ojala; Leena Paakkari (BMC, 2023)
Abstract Background The COVID-19 pandemic has had implications for adolescents' interpersonal relationships, communication patterns, education, recreational activities and well-being. An understanding of the impact of the pandemic on their mental health is crucial in measures to promote the post-pandemic recovery. Using a person-centered approach, the current study aimed to identify mental health profiles in two cross-sectional samples of Finnish adolescents before and after the peak of the pandemic, and to examine how socio-demographic and psychosocial factors, academic expectations, health literacy, and self-rated health are associated with the emerging profiles. Methods and findings Survey data from the Health Behaviour in School-aged Children (HBSC) study conducted in Finland in 2018 (N = 3498, age M = 13.44) and 2022 (N = 3838, age M = 13.21) were analyzed. A four-profile model using cluster analysis was selected for both samples. In Sample 1, the identified profiles were (1) "Good mental health", (2) "Mixed psychosocial health", (3) "Somatically challenged", and (4) "Poor mental health". In Sample 2, the identified profiles were (1) "Good mental health", (2) "Mixed psychosomatic health", (3) "Poor mental health and low loneliness", and (4) "Poor mental health and high loneliness". The results of the mixed effect multinomial logistic regression analysis showed that in both samples, being a girl and reporting lower maternal monitoring; lower family, peer, and teacher support; higher intensity of online communication; a less positive home atmosphere and school climate; and poor self-rated health were most strongly linked to belonging to a poorer mental health profile. In addition, in Sample 2, low subjective health literacy was a key factor associated with poorer mental health profiles, and teacher support was more important than before COVID. Conclusions The current study stresses the importance of identifying those vulnerable to developing poor mental health. To maximize post-pandemic recovery, the role of schools, especially teacher support and health literacy, along with the factors that remained important over time should be taken into account in public health and health promotion interventions.